Dinâmica de Bemisia tabaci biótipo B (Hemiptera: Aleyrodidae) na cultura de tomateiro com adubação mineral e orgânica em ambiente protegido - Soares, Cristina Gomes (2012)
The whitefly is a major pest of tomato due to direct damage by sucking sap and favoring the appearance of sooty mold and indirect caused as transmitting various viruses.Aiming to improve the physiological conditions of tomato by use of mineral and organic fertilizers was assessed incidence and dynamics of whitefly colonization in tomato plants grown in a greenhouse. The experiment was conducted at the School of St. Louis (FESL), State University of Maranhão (UEMA), in a greenhouse, from November 2010 to December 2011. The experimental design was completely randomized with five treatments and six replications in a factorial 3x5, factor 1 (evaluation periods) and factor 2 (combined treatments with different types of fertilization). The number of eggs and nymphs of Bemisia tabaci was evaluated by counting performed at 45, 60 and 75 days after transplanting. In the sampling process were removed three leaflets per plant, one-third of each plant (lower, middle and upper). For the analysis of soluble fractions (sugars, ammonium, nitrate and amino-N) used the same leaflets were collected for counting of eggs and nymphs of whitefly. There was significant difference in the mean number of eggs and nymphs of B. tabaci in organic fertilization treatment differed significantly from mineral fertilizer. The median and apical strata were most preferred for oviposition and feeding nymphs differed significantly from that presented the lowest incidence. Regarding the evaluation periods at 60 and 75 days were larger infestations B. tabaci independent regions of the plant analyzed. For the concentrations of N-NO3-were initially high in all treatments, significant difference for the organic treatment. As for the content of N-NH4 + significant difference between the treatments at 45 days and only to the witness and between the evaluation periods were no significant differences for all treatments except the organic treatment, and the highest concentrations were observed at the second independent evaluation of the treatment.